Psychological determinants of COVID-19 vaccine acceptance among urban slum dwellers of Bangladesh - Muhammad Mainuddin Patwary; Muhammad Mainuddin Patwary; Mondira Bardhan; Mondira Bardhan; Sardar Al Imran; Sardar Al Imran; Mehedi Hasan; Mehedi Hasan; Faiza Imam Tuhi; Faiza Imam Tuhi; Sama Jamila Rahim; Sama Jamila Rahim; et al. (Frontiers Media S.A., 2022)
IntroductionCoronavirus disease 2019 (COVID-19) vaccination has emerged as a promising approach to counter the harmful impacts of the pandemic. Understanding the psychological components that may impact an individual's attitude toward COVID-19 vaccination is crucial for generating evidence-based ways to minimize vaccine hesitancy. This study determined the psychological antecedents regarding vaccine acceptance among urban slum people of Bangladesh.MethodsFrom 5 July to 5 August 5, 2021, a face-to-face survey was conducted in the urban slum of two large cities in Bangladesh. The questionnaire considered socio-demographics, health-related characteristics, psychological determinants, sources of information, and conspiracy beliefs regarding COVID-19. The 5C sub-scales were used to assess psychological antecedents. Five stepwise binary logistic regression models evaluated significant predictors for confidence, complacency, calculation, constraints, and collective responsibility. Multinomial logistic regression was used to determine the relationship between psychological antecedents and vaccine acceptability.ResultsThe study revealed that the slum residents with a high level of confident (89.94%), complacent (72.73%), having constraints (82.31%), calculative (84.80%), and responsible (93.30%) showed a higher vaccine acceptance rate. Higher vaccine acceptance was related to the believer in natural-made origin (85.96%) and those who rejected anti-vaccination (88.44%). The information acquired from newspapers differed significantly (p < 0.05), though TV or radio was the most common primary information source about COVID-19 vaccines (74.75%). The regression result revealed that marital status, education, family income, and perceived health condition were significantly associated with the 5C domains. Two psychological antecedents including complacency (OR = 3.97; p < 0.001) and collective responsibility (OR = 0.23; p < 0.001) were significantly associated with vaccine acceptance.ConclusionsDifferent predictors significantly affect psychological antecedents related to COVID-19 vaccine uptake. Therefore, considering the factors, targeted actions based on the findings may help to lower vaccine reluctance and boost vaccination rates.